Effects of a Thermosensitive Antiadhesive Agent on Single-Row Arthroscopic Rotator Cuff Repair. Issue 11 (September 2020) - Kim, Jangwoo; Kim, Yuna; Jung, Whanik; Nam, Ji Hoon; Kim, Sae Hoon
Background: Postoperative stiffness after rotator cuff repair is a common complication that can lead to poor outcomes and patient discomfort. The application of an antiadhesive agent at the time of repair recently became an option for clinicians, but little information is available on its effects. Purpose: To evaluate and compare retear rates, the incidence of postoperative stiffness, and the clinical outcomes of patients who underwent cuff repair with or without the application of an antiadhesive agent. Study Design: Cohort study; Level of evidence, 3. Methods: Among 296 patients who underwent arthroscopic rotator cuff repair surgery, we compared the outcomes of those injected with a thermosensitive gel antiadhesive agent into the subacromial space (112 cases) versus noninjected controls (184 cases). Retear rates in the 2 groups were determined by magnetic resonance imaging at 1 year after surgery. Shoulder joint range of motion and functional scores were evaluated serially. Results: The rate of retear was significantly lower in the injection group (20/112 cases; 17.9%) than the control group (53/184 cases; 28.8%) ( P = .034). Postoperative stiffness was not significantly different between the 2 groups ( P = .710). Among the data regarding range of motion, only forward flexion at 6 months after surgery showed superior results in the injection group. Functional scores showed conflicting results: The control group had better visual analog scale scores for pain (injection vs control: 2.17 vs 1.68 at 6 months; 1.82 vs 1.28 at 12 months), American Shoulder and Elbow Surgeons scores (79.89 vs 89.64 at 12 months), and simple shoulder test scores (8.70 vs 10.06 at 12 months), whereas the injection group had better Constant-Murley scores (injection vs control: 59.49 vs 55.60 at 3 months; 77.35 vs 71.98 at 6 months; 87.28 vs 81.56 at 12 months). Conclusion: The tendon healing rate was significantly higher in the group receiving an antiadhesive agent than in the control group. No intergroup difference was seen in the occurrence of postoperative stiffness. However, the pain-related functional score showed inferior results in the injection group at 12 months. The biological action of antiadhesive agents in rotator cuff repair should be further evaluated.